Web application of knowledge management in broiler production in agriculture for vocational education - Wuttikorn, Injana; Ratchadakorn, Phonpakdee; Pakkapong, Poungsuk; Sirirat, Petsangsri (My University, 2019)
This study aimed to: 1) construct and find the efficiency of web application of knowledge management in broiler production and 2) test and find the learning achievement after using the Web application. The research instruments in this study were: 1) an assessment form for the efficiency of the web application of knowledge management in broiler production and the web application was assessed by 7 specialists and 2) learning achievement test in the production of commercial broilers was used by 100 students in the program of higher vocational certificate at 4 Colleges of Agriculture and Technology in Thailand. The data were analyzed by using the mean, standard deviation, and independent sample t-test. The results of the study revealed that the efficiency of web application has a high level. The pretest-posttest control group design was used in the comparison of control groups (45 students who did not use the web application) and experimental group (55 students who use the web application). The results found that the experimental group had mean score higher than the control group significantly at the level of 0.05.
Keywords: Broiler production; Knowledge management; Learning achievement; Vocational education; Web application